Service with A Smile and Encounter Satisfaction: Emotional Contagion and Appraisal Mechanisms - Barger, Patricia B.; Grandey, Alicia A. (Academy of Management Journal, 2006)
Primitive emotional contagion has been proposed to explain why “service with a smile” predicts encounter satisfaction. We provide a comprehensive test of this mechanism by examining mimicry and mood as mediators in service encounters, contrasting such mediation with a direct path through perceived service quality. Independent coders recorded the strength of employees' and customers' smiles at three points in time during real service encounters, and 173 customers completed postencounter surveys. Mimicry effects were supported; however, only service quality appraisals, and not customers' affect, fully mediated the relationship of employee smiling and encounter satisfaction.